2015
DOI: 10.1088/0963-0252/24/5/055023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fine bubbles on electric discharge in water

Abstract: Ar or O 2 fine bubbles of diameter <80 μm were introduced in water and a pulsed discharge plasma was generated between cylinder electrodes in water. Fine bubbles in water affected discharge ignition and caused low inception voltage and suppression of rising temperature. The contamination from electrodes was suppressed in the case of fine bubbles addition because fine bubbles assisted plasma generation. In addition, discharge with fine bubbles enhanced plasma emission with high electron density compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 38 publications
3
18
0
1
Order By: Relevance
“…Also, the variation of n e as a function of EC is not significant in both liquids. For the in-water discharges, the order of n e is in good agreement with that reported in literature [24,25]; however, for the in-methanol discharges, present estimation of n e is relatively high compared to the reported data [12]. Concerning the effect of EC on the electron density, Vanraes et al [24] also reported that n e is almost independent of EC, although their reported electron density based on Hα for 5 mS/cm is slightly smaller than that of distilled water.…”
Section: Characterization Of Dischargessupporting
confidence: 90%
“…Also, the variation of n e as a function of EC is not significant in both liquids. For the in-water discharges, the order of n e is in good agreement with that reported in literature [24,25]; however, for the in-methanol discharges, present estimation of n e is relatively high compared to the reported data [12]. Concerning the effect of EC on the electron density, Vanraes et al [24] also reported that n e is almost independent of EC, although their reported electron density based on Hα for 5 mS/cm is slightly smaller than that of distilled water.…”
Section: Characterization Of Dischargessupporting
confidence: 90%
“…During discharge plasma formation with the working gas of air or nitrogen, HNO 3 could be generated (NO 3 − concentration 15.45 mg L −1 at 120 min by DBD treatment in our study), acidifying the solution . A buffer solution therefore was added so as to evaluate the influence of pH value as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…В [24] с помощью компьютерного моделирования показано, что разряд в пузырьке газа, помещенного в жидкость с высокой диэлектрической проницаемостью, развивается вдоль ее поверхности. Подробно вопросы развития разряда в пузырьках газа в жидкости рассмотрены в ряде работ, в частности [7,[25][26][27][28].…”
Section: экспериментальные результаты и обсужденияunclassified